Analisis Pembiayaan Dana Talangan Haji Perspektif Etika Bisnis Islam - Dewi Rahayu; Ismail Marzuki (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2020)
Islamic financial institutions have experienced significant developments, including in the development of financing products in the form of hajj bailout funds. In accordance with DSN-MUI fatwa No. 29 / DSN-MUI / III / 2002 hajj bailout funds using the qard and ijarah agreements given to prospective pilgrims with the aim of obtaining the portion of the hajj list or BPIH (the cost of the pilgrimage). the need to review from the perspective of Islamic business ethics in order to see the extent to which the implementation of the hajj bailout fund is in accordance with ethical business principles and Islamic sharia principles. The method used is a qualitative research method using the literature study approach in books, journals, and fatwas of the National Sharia Council. The results showed that the negative effect caused by the implementation of the hajj bailout fund is caused by the implementation of the hajj bailout fund not in accordance with Islamic business ethics and principles.